Design and Implementation of Questionnaire for the Evaluation of Medical Students' Morning Report Program in Internal Medicine Ward of Sina Hospital in Tehran University of Medical Sciences - Ahmad Salimzadeh; Effat Razeghi; Rayka Jamali (Babol University of Medical Sciences, 2016)
BACKGROUND AND OBJECTIVE: The purpose of this study was to design and evaluate the medical students' morning report program in internal medicine ward of Sina Hospital, Tehran University of Medical Sciences. METHODS: First, the educational program was developed in the form of a development plan for education according to the Kern Steps. A questionnaire was used to evaluate the study that had designed based on Special-purpose process. It contained 14 questions and was graded as Likert scale (1-3). The medical students filled out the questionnaire as a pre-test and post-test at the end of training. The result of this questionnaire was a measure of trainees' change in awareness, performance, and skill after the completion of research. FINDINGS: The implementation of the educational process since the beginning of 2010 was 15 months. Validity and reliability of the questionnaire was investigated in 20 trainees and the results were good. The survey result of 70 trainees of this process showed  that  the educational program lead to increase awareness from students;#39 morning report, their self-steam while visiting the patient, dominance in the clinical findings of patients, fluency and appropriate presentation, clinical reasoning and motivation for taking patient;#39s history. CONCLUSION: The new designed questionnaire in this research seems to be an appropriate tool for evaluation of clinical courses in morning report.